A3 Adenosine Receptors from Cell Biology to Pharmacology and Therapeutics - Borea, Pier Andrea (Springer Netherlands : Imprint: Springer, 2010)
This Book "A3 Adenosine Receptors from Cell Biology to Pharmacology and Therapeutics " documents the present state of knowledge of the adenosine A3 receptor. Adenosine A3 receptors are G protein-linked receptors that function in physiology and intracellular signaling and are involved in inflammatory responses and mediating cell proliferation and cell death. The A3 receptor is increasingly being recognized for its biological roles throughout the body, and many A3 receptor ligands have proven useful in elucidating peripheral and central pathologies. This book covers a wide range of information including data from studies of theoretical, molecular and cellular pharmacology, signal transduction, integrative physiology, new drug discoveries and clinical applications. The book includes sections on: A3 Adenosine Receptor signal transduction Adenosine Receptor medicinal chemistry Effects and therapeutic applications of Adenosine Receptors on tissues and organs Adenosine Receptors and inflammatory and auto-immune diseases Adenosine Receptors and cancer The chapters in this book cover both fundamental science and relevant applications and provide an authoritative account of the current status of the field. "A3 Adenosine Receptors from Cell Biology to Pharmacology and Therapeutics" is an up to date and scientifically excellent source of information, attractive to basic and clinical scientists alike.